Reproductive profile of jersey bovine females in a herd of Três Barras do Paraná, PR, Brazil: Case report - Pereira, A. R.; Pinto Neto, A.; Oliveira, W.; Becher, B. G.; Mota, M. F.; Merlini, L. S. (Scientific Electronic Archives, 2018)
Agribusiness, as well as cattle production, contributes to the Brazilian economy, highlighting Brazil in the fifth place in the world ranking of milk production. The Jersey breed participates in this context, where the females are smaller and productive, they present high concentration of fat and protein in the milk, besides needing smaller area destined to the handling and creation. In order for the productive system of milk to be effective, there is a need for reproductive follow-up of the animals, especially of the pubescent females, avoiding compromising reproductive indices, such as the calving interval, which results in financial losses to the producer. Thus, we analyzed reproductive data of a commercial application (Procreare PlusR), used in a dairy farm, from the municipality of Três Barras, Paraná, from January 2014 to June 2017. The herd, composed of 58 pubescent females Jersey, is created in a semi-intensive system, using basically family labor. Data were tabulated and analyzed in descriptive form. The mean age of the females studied was 5.5 years, with 8.62% (5/58) of them being heifers, 34.48% (20/58) primiparous, 41.52% (24/58) cows with two calving and 15.52% (9/58) cows with three calving. The calving interval (CI) of the females was 369 + 29.16 days, being 349 ± 2.33 and 390.25 + 27.22 days for females who had two and three calving, respectively. The mean number of services per conception was 1.2, being 1, 1.35, 1.12 and 1.28 for heifers, primiparous, with two and three calving, respectively. When considering the seasons, we observed 1.14, 1.93, 1.76 and 1.53 services/conception in the spring (September-November), summer (December-January), fall (March - April) and winter (May- August), respectively. It is concluded that studied Jersey herd presents adequate zootechnical indexes, regarding the interval of calving and services / conception, possibly as a reflection of the adequate conditions of the management practices and zootechnical control.